Penerapan Layanan Bimbingan Kelompok Dalam Mengembangkan Konsep Diri Pada Siswa Kelas VIII MTS AR RIDHA - Nurjannah Salsabila Simanungkalit; Uli Makmun Hasibuan; Reva Lina Aulia; Arzela Azrina (Kampus Akademik Publiser, 2026)
Adolescence is a crucial phase in the formation of self-concept, which influences students' self-confidence and learning motivation. This study aims to describe the implementation of group guidance services in developing the self-concept of eighth-grade students at MTs Ar-Ridha. The research method used was descriptive qualitative. The research subjects consisted of 5 eighth-grade students who participated in a 25-minute group guidance session on the topic of